The evolution of Goth culture : the origins and deeds of the new Goths - Spracklen, Karl; Spracklen, Beverley (Emerald studies in alternativity and marginalization., 2018)
In this book, Spracklen and Spracklen use the idea of collective memory to explore the controversies and boundary-making surrounding the genesis and progression of the modern gothic alternative culture. They suggest that the only way for goth culture to survive is if it becomes transgressive and radical again.